An analysis of privacy in the space organisation of traditional Malay houses in peninsular Malaysia - Abdul Rahim, Zaiton; Abdul Majid, Noor Hanita; Denan, Zuraini; Mohd Nawawi, Norwina (American Scientific Publishers, 2017)
This study contested that privacy was important in the traditional Malay culture and was translated into the traditional Malay houses despite suggestions that privacy was not given emphasis in the traditional Malay society. The study employs analysis of plans of traditional Malay houses from different states in Malaysia to evaluate consideration for privacy in the traditional Malay houses in relation to the conception of privacy and privacy regulation in traditional Malay culture. The results show that privacy was provided in the traditional Malay houses consistent with the conception of privacy which emphasis on community intimacy, the role of women in the house, respect for elders and modesty. Privacy of individual privacy was not emphasised as in the Western cultures. Findings also indicated that different level of privacy was provided at both public and private level in the house through the space organisation, design of openings within each of the traditional Malay houses and regulated by traditional Malay culture which is coterminous with Islam as a way of life as important privacy regulating mechanisms. Differences in terms of level of privacy required influenced the traditional houses in different states.